2021
DOI: 10.1159/000517153
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Clinical and Laboratory Findings of Asthmatic Children with SARS-CoV-2 Infection

Abstract: <b><i>Introduction:</i></b> There are a limited number of studies about the clinical findings of coronavirus infection in pediatric patients with asthma. We aimed to evaluate the clinical and laboratory characteristics of pediatric patients with asthma and healthy children without chronic disease who infected with SARS-CoV-2. <b><i>Methods:</i></b> This is a retrospective, case-control study comparing the asthma diagnosed and healthy children who were diagnosed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 30 publications
2
21
0
1
Order By: Relevance
“…Results remained essentially unchanged after further adjusting for non‐asthma‐related symptoms that could have independently increased likelihood of hospitalization, such as fever, vomiting, and fatigue. Consistent with our results, some studies have reported asthma as a risk factor for hospitalization in children with COVID‐19, 26 , 27 while others have reported conflicting results. 20 , 22 Although our sample size was small and thus results need to be interpreted with caution, hospital LOS and the need for respiratory support or PICU admission did not seem to differ by asthma status.…”
Section: Discussionsupporting
confidence: 92%
“…Results remained essentially unchanged after further adjusting for non‐asthma‐related symptoms that could have independently increased likelihood of hospitalization, such as fever, vomiting, and fatigue. Consistent with our results, some studies have reported asthma as a risk factor for hospitalization in children with COVID‐19, 26 , 27 while others have reported conflicting results. 20 , 22 Although our sample size was small and thus results need to be interpreted with caution, hospital LOS and the need for respiratory support or PICU admission did not seem to differ by asthma status.…”
Section: Discussionsupporting
confidence: 92%
“…In children, the prevalence of asthma in COVID-19 patients was lower compared with that in the pediatric population ( 58–60 ). Asthma was not associated with increased severity and mortality of COVID-19 ( 61 ). On the other hand, improved asthma control and improved lung function were observed in children with asthma during the COVID-19 pandemic, which may be due to reduced exposure to asthma triggers and increased adherence to asthma treatments ( 62 ).…”
Section: Asthma and Covid-19mentioning
confidence: 87%
“…symptoms in asthmatic and non-asthmatic pediatric patients was found to be 94.4% and 85.8%, respectively, and no statistically significant difference was found between the two groups. 14 The presence and duration of fever did not differ significantly between the two groups. In retrospective studies in childhood, fever was reported to be 50.4% in our country and 51.2% in the USA which are similar to our study.…”
Section: Discussionmentioning
confidence: 83%
“…Similarly, in the study conducted in our country, no significant difference was found between the asthma‐controlled and uncontrolled groups in terms of having symptoms of COVID‐19, being hospitalized due to COVID‐19, prescribing COVID‐19 treatment, and requiring oxygen and steroid treatment. 14 In a study conducted in Spain, it was reported that asthma severity and control status were not associated with a worse clinical course. 15 All our patients had mild or moderate asthma, and we did not have any severe asthma cases.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation